1990
DOI: 10.2105/ajph.80.7.853
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for syphilis: cocaine use and prostitution.

Abstract: In Philadelphia, a large increase in syphilis among minority group heterosexuals began in 1986 and preceded similar increases elsewhere in the United States. To determine reasons for this increase, we conducted a case-control study in the metropolitan sexually transmitted diseases clinic during 1987 and 1988. Cocaine use (odds ratio [OR] 3.1; 95% confidence interval [95% CI] = 1.5, 6.5 among men; OR 5.8; 95% CI = 1.5, 33 among women) and exchange of drugs for sex (OR 3.5; 95% CI = 1.4, 8.7 among men) were ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(62 citation statements)
references
References 17 publications
1
59
1
1
Order By: Relevance
“…The probability of exposure to an infected partner is also higher if the partner has used crack cocaine (58,81). This particular risk behavior is strongly associated with other risk behaviors, including exchange of sex for cocaine or money, sex with multiple partners, sex with anonymous partners, and a history of STDs.…”
Section: Likelihood Of Exposure To An Infected Partnermentioning
confidence: 99%
“…The probability of exposure to an infected partner is also higher if the partner has used crack cocaine (58,81). This particular risk behavior is strongly associated with other risk behaviors, including exchange of sex for cocaine or money, sex with multiple partners, sex with anonymous partners, and a history of STDs.…”
Section: Likelihood Of Exposure To An Infected Partnermentioning
confidence: 99%
“…At the same time, it has been demonstrated that the use of illegal drugs is common among both commercial sex workers and sex traders (Campbell, 1991;Goldstein, 1979;Inciardi et al, 1991;Miller, 1986;Rolfs et al, 1990;Rosenberg and Weiner, 1988;Sterk, 1988Sterk, , 1999. Of particular significance have been studies suggesting that crack use promotes the heterosexual transmission of HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have established an association between cocaine dependence and psychiatric symptomatology-in particular, antisocial and borderline syndromes. '5"6 Crack-addicted sex workers, who report low rates of condom use and high numbers of sexual partners, [17][18][19][20][21][22] may be especially vulnerable to psychological distress because of the degrading and perilous circumstances they face when exchanging sex for money or drugs. '7-24 Previous research has also documented associations between psychological distress and dependence on opiates25'26 and alcohol,27'28 both of which are also associated with sex trading.…”
Section: Introductionmentioning
confidence: 99%